Skattekort på nätet – exempel på hur Skatteförvaltningen utvecklar sina elektroniska tjänster - Hoffrén, Kaj (Klart språk i Norden, 2014)
Tax card online is an e-service offered by the Finnish Tax Administration to anyone who needs to change their tax card in the course of the year. Prior to implementation, the usability of the service was tested with the help of a company specializing in Internet services. An additional usability test was made prior to its launch, where a group of customers were invited to test the service and give their feedback on it. In order that the service should be perceived as easy and user-friendly, the language and instructions have been made as simple as possible. The Tax Administration hired language advisors to write the texts. Translations were done by professional translators. Going forward, customer response will play a big part in the development of the service. There is an online feedback form available to users. Customer response regarding incoming requests for support is also followed up. Usability is examined approximately every two years, looking specifically at the age of the customers, how familiar they are with the service and which parts of the service have been considered problematic.